2015
DOI: 10.1039/c4ra14277b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced shape memory performance of polyurethanes via the incorporation of organic or inorganic networks

Abstract: A diol compound with a reactive azetidine-2,4-dione group was prepared and introduced as a side chain moiety of poly(3-caprolactone) (PCL) based polyurethane (PU). The PUs with reactive pendants were crosslinked by 1,6-diaminohexane, or modified by an alkoxysilane (3-aminopropyltriethoxysilane, APTS) followed by a sol-gel reaction to bring about crosslinked PUs for shape memory applications. Thermal and mechanical properties of the crosslinked PUs are strongly dependent on the chemical structure of the interch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…). ATR‐FTIR was used to assess the formation of polyurethanes . Chemical structure of the resultant SMPUs was fully confirmed and results were reported in a previous work .…”
Section: Resultssupporting
confidence: 62%
“…). ATR‐FTIR was used to assess the formation of polyurethanes . Chemical structure of the resultant SMPUs was fully confirmed and results were reported in a previous work .…”
Section: Resultssupporting
confidence: 62%
“…To develop shape memory materials, a polymer exhibits both a large modulus difference during transition range and a lengthy rubbery plateau. For segmented polyurethanes, the shape deformation can be realized via the reversible phase transition such as glass transition from the soft segment, while the shape recovery could be bound via strong hydrogen-bonding interactions from the hard segment . It is noted that the presence of strong hydrogen bonding from the urethane linkages can achieve sufficient physical cross-linking to exhibit elastomeric properties, without resorting to either chemical cross-linking or crystallinity for linear segmented PUs .…”
Section: Resultsmentioning
confidence: 99%
“…By incorporation of cardo five-membered ring structures into the PUs (Scheme S1), we have found that the resulting polymers were imparted with certain distinctive mechanical and morphological properties as compared to those of the PUs based on common bisphenols. These cardo-type PUs exhibited a large modulus variation at glass transition, and an extended rubbery plateau in dynamic mechanical analyses, which might be fit for shape memory materials. …”
Section: Introductionmentioning
confidence: 97%
“…This can be explained with the greater macromolecular chain mobility toward a greater degree of order after the addition of the active moieties, as part of the hard segment. 27 Thermal transitions relative to the materials soft segment melting temperature (T m ) can be observed in the range of 156 to 170 °C, explained with the high hard segment content. 28 The decrease in T m values, from 189 °C for TPUr to 145 °C for TPU-QPS-TOP, was explained with the addition of the ionic moieties, reflecting again the greater polymer chains mobility and less thermally stable crystalline domains (Figure 5).…”
Section: ■ Introductionmentioning
confidence: 99%